2005
DOI: 10.1136/thx.2004.038208
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of brain-derived neurotrophic factor (BDNF) during sleep apnoea treatment

Abstract: Background: Patients with obstructive sleep apnoea syndrome (OSAS) often display persistent cognitive dysfunction despite effective treatment with continuous positive airway pressure (CPAP). Brain-derived neurotrophic factor (BDNF) is a key mediator of memory and cognition, but its regulation in OSAS and during CPAP treatment is unknown. Methods: Serum and plasma BDNF concentrations, BDNF secretion by peripheral blood mononuclear cells, and overnight polysomnography were evaluated in 17 men with newly diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 30 publications
(24 reference statements)
3
26
1
Order By: Relevance
“…Although BDNF gene polymorphism has not been previously studied in OSAS patients, some studies investigated the serum and plasma levels of BDNF protein in this patient group. A marked decrease was observed in the serum and plasma The remaining data are shown as mean ± standard deviation Lung BDNF levels of OSAS patients following an overnight CPAP therapy [9]. Before therapy, serum and plasma BDNF levels of these patients were similar to the healthy individuals, and the authors attributed the significant BDNF decrease noted after CPAP therapy to the enhanced neuronal demand [9].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Although BDNF gene polymorphism has not been previously studied in OSAS patients, some studies investigated the serum and plasma levels of BDNF protein in this patient group. A marked decrease was observed in the serum and plasma The remaining data are shown as mean ± standard deviation Lung BDNF levels of OSAS patients following an overnight CPAP therapy [9]. Before therapy, serum and plasma BDNF levels of these patients were similar to the healthy individuals, and the authors attributed the significant BDNF decrease noted after CPAP therapy to the enhanced neuronal demand [9].…”
Section: Discussionmentioning
confidence: 95%
“…A marked decrease was observed in the serum and plasma The remaining data are shown as mean ± standard deviation Lung BDNF levels of OSAS patients following an overnight CPAP therapy [9]. Before therapy, serum and plasma BDNF levels of these patients were similar to the healthy individuals, and the authors attributed the significant BDNF decrease noted after CPAP therapy to the enhanced neuronal demand [9]. In another study, serum and plasma BDNF levels of children with OSAS were found to be significantly decreased 3 months after adenotonsillectomy [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Brain-derived neurotrophic factor is also involved in the cognitive dysfunction that occurs in patients with OSAS. 30 In addition,…”
Section: Regulation Of Bdnf In Obstructive Sleep Apnoeamentioning
confidence: 99%
“…It is characterized by repeated and/or periodic cessation of breathing during sleep due to partial or complete upper airway, oropharyngeal, obstruction. In addition, OSA also causes significant sleep disturbances resulting in daytime sleepiness and exhaustion which may lead to traffic accidents [2] or cognitive dysfunction, including memory, problem solving, and behavioral performance deficits [3]. Additionally, OSA and metabolic syndrome are related.…”
Section: Introductionmentioning
confidence: 99%